Hydroxycamptothecin Inhibits Peritendinous Adhesion via the Endoplasmic Reticulum Stress-Dependent Apoptosis - Yao, Zhixiao; Wang, Wei; Ning, Jiexin; Zhang, Xiangqi; Zheng, Wei; Qian, Yun; Fan, Cunyi (Frontiers in Pharmacology, 2019)
Traumatic peritendinous fibrosis is a worldwide clinical problem resulting in severe limb disability. Hydroxycamptothecin (HCPT) is an anti-neoplastic drug widely exploited in clinical practice. It has shown the potential of anti-fibrosis in recent years. We previously demonstrated that HCPT inhibited the characterization of fibrosis in vitro. However, it is still unclear whether it ameliorates peritendinous adhesion in in vivo animal tendon injury model. The underlying mechanism is also worthy of investigation. The present study aimed to determine whether HCPT inhibited tendon adhesion and to explore the underlying mechanisms. In a rat tendon injury model, we observed that topical application of HCPT significantly attenuated peritendinous adhesion displayed by the results of macroscopic observation, biomechanical, histological, immunohistochemical evaluation, western blot, and quantitative PCR (q-PCR) analyses. Furthermore, western blot and q-PCR analyses revealed that this phenomenon was correlated with HCPT activation of endoplasmic reticulum (ER) stress. In addition, in vitro studies showed that HCPT significantly inhibited fibroblast proliferation and induced apoptosis to reduce the expression of extracellular matrix (ECM) proteins COL3A1 and α-smooth muscle actin (α-SMA). Finally, we employed small interfering RNA (siRNA) targeting inositol requiring kinase 1 (IRE1) and activating transcription factor 6 (ATF-6) to verify that anti-fibrotic effect of HCPT was mediated by the ER-dependent apoptotic pathway. In conclusion, our results indicated that HCPT inhibited peritendinous fibrosis by the ER-dependent apoptotic pathway and it might serve as a potential solution to the prevention of traumatic peritendinous adhesion.